The constant term in the expression 1 + x^{2}+ x is
The coefficient of y^{3 }in the expression y − y^{3}+ y^{2}is
Coefficient is the numerical number associated with the variable. So here we have (1)y^{3}. So the answer is 1.
Multiply 2a and 3a.
multiplication of a number with variable gives multiplication of integer with integer and variables with variables
in given question, it'll lead to
2a x 3a = 6a^{2}
Get the algebraic expressions for subtraction of z from y.
Find the value of x + 4 for x = 2.
Find the product of (2x+3y)(2x+3y).
Applying (a+b)^{2 }= a^{2}+ b^{2}+2ab
so,(2x+3y)^{2 }= (2x)^{2}+2*2x*3y+(3y)^{2 }= 4x^{2}+12xy+9y^{2}
When terms have the same algebraic factor, they are called __________.
An expression which contains two unlike terms is called _______.
A _________ can take various values.
What degree does x^{3}  x^{2}y^{2}  8y^{2}+ 2 have?
The largest such degree is the degree of the polynomial.
Here, there are 2 variables so the largest exponent of variables (x & y) is 4 i.e (2+2).
Simplify these expressions and find their values, if x = 3, a = – 1, b = – 2.
3x – 5a – x^{2} + 9b
3x  5a x 2 + 9b = 3*3  5(1)32 + 9 (2) = 9 + 5 9  18 = 5  18 = 13
Simplify these expressions and find their values, if x = 3, a = – 1, b = – 2.
2b – 8x +4x^{2} + 4a
2b8x+4x^{2}+4a
=2(2)8(3)+ 4(3)^{2}+4(1)
=424+364
=4
Simplify combining like terms: 3a – 2b – ab – (a – b + ab) + 3ab + b – a
Which of the following is obtained by subtracting x^{2}y^{2} from y^{2 } x^{2}?
y^{2}x^{2}(x^{2}y^{2})=y^{2}x^{2}x^{2}+y^{2}=2y^{2}2x^{2}=2(x^{2}y^{2})
What should be taken away from 3x^{2}− 4y^{2}+ 5xy+ 20 to obtain −x^{2}−y^{2}+ 6xy+ 20?
3x^{2 } 4y^{2 }+ 5xy + 20 (x^{2 } y^{2 }+ 6xy+20)
=3x^{2 } 4y^{2 }+ 5xy + 20 + x^{2} + y^{2 } 6xy20)
=4x^{2}3y^{2}xy
The number of terms in the expression 1.2ab – 2.4 b + 3.6a is
What is the numerical coefficient of y^{2}in the expression 2x^{2}y  15xy^{2 }+ 7y
The simplified form of the Boolean expression (X + Y + XY)(X + Z) is
=(x+y(1+x))(x+z)
=(x+y)(x+z)
=x.x+x.z+y.x+y.z
=x+xz+yx+yz
=x(1+z)+yx+yz
=x+yx+yz
=x(1+y)+yz
=x+yz
The expression xyz is
From the following expressions 10pq, 7p, 8q, −p^{2}q^{2}, 7pq, 23, ab, 3a, b.The like terms are
Use Code STAYHOME200 and get INR 200 additional OFF

Use Coupon Code 







